Hands-on cybersecurity for architects plan and design robust security architectures - Rerup, Neil; Aslaner, Milad (Packt Publishing Ltd., 2018)
Hands-On Cybersecurity for Architects will help you to successfully design, integrate, and implement complex security structures in any solution whilst ensuring that the solution functions as expected. Basic understanding of network and computer security implementation will be helpful. This book is also ideal for non-security architects who want to understand how to integrate security into their solutions.